Osteoporosis and Health-Related Quality of Life Among Older Women - Wilson, Ashley; Maiocco, Gina; Sambamoorthi, Usha (Universitas STRADA Indonesia, 2020)
Background: Osteoporosis, a systemic skeletal disease characterized by low bone mass, poses a significant disease burden for older women. Often assessed using Health-Related Quality of Life (HRQoL) scale, the association between osteoporosis and HRQoL is scarce, with the majority of quality of life studies focused on osteoporotic women post fracture. Purpose: The study’s primary objectives were to examine if differences exist in HRQoL among women greater than 50 years of age who have and/or do not have osteoporosis and to gain insight into the relationship of HRQoL and osteoporosis.Methods: A retrospective cross-sectional design involving data extraction on women aged 50 years or older from 2014 Medical Expenditure Panel Survey (MEPS) was used (N = 4,661). HRQoL was measured by the generic Short-Form-12 Version 2 Physical (PCS) and Mental Health (MCS) component summary scores. The differences between osteoporosis and PCS and MCS were examined using t-tests and multivariable ordinary least squares regression.Results: Overall, 4.1% women aged 50 and older had osteoporosis. In both bivariate and multivariable analyses, no statistically significant differences were observed in HRQoL measures between women with and/or without osteoporosis. Conclusion: No group differences in HRQoL by osteoporosis status suggest the need for additional research using other research methodologies to flush out nuances in QOL changes. Clinician actions focused on insured and uninsured women with osteoporosis must include early and ongoing QOL assessment, with a focus on physical changes overtime